Cryptogenic stroke in a young patient after COVID-19 infection – a case report - Liyanage, L.R. Sathisha Deshan; Purvishbhai, Soni Karsh; Antipina, Ekaterina Olegovna (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Cryptogenic stroke (CS) is a type of cerebral ischemia in which the cause is unknown or unclear. It can be difficult to determine the cause of CS because of various factors, such as incomplete investigations or the transient or reversible nature of the event. Infections can increase the risk of stroke by causing localized inflammation of the meninges and cerebral parenchyma, systemic inflammation, coagulation, and endothelial dysfunction. COVID-19-related cerebrovascular events can happen due to a hypercoagulable state from systemic inflammation and cytokine storm, post-infectious immune-mediated responses, and direct viral-induced endothelitis, which can lead to angiopathic thrombosis. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. A 25-year-old male was diagnosed with mild semantic aphasia. The patient had a history of moderate COVID-19 infection. An angiography revealed that the M2 segment of the middle cerebral artery in the left hemisphere was not contrasted, indicating an occlusion. MRI and CT scans showed evidence of ischemic changes in the left hemisphere of the brain. The patient was treated with several drugs, including antiplatelet and neuroprotective drugs. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Our case demonstrates that autoimmune antibody formation, specifically antinuclear antibodies, can cause vasculopathy, leading to thrombus formation and stroke. It suggests a potential link between autoimmune antibody formation and stroke in COVID-19 patients.